A Simplified Digital Approach to the Treatment of a Postpuberty Patient with a Class III Malocclusion and Bilateral Crossbite. (30th September 2021) - Aiello, Domenico; Nucera, Riccardo; Costa, Stefania; Figliuzzi, Michele Mario; Paduano, Sergio
Abstract : Monolateral and bilateral crossbites are amongst the most frequent forms of malocclusion in the world population. The lack of early correction of this type of malocclusion leads to the partial or total ossification of the sutures which then require surgical treatment in adult patients. In recent years, devices on minipalatal screws have noticeably increased the time window in which it is possible to correct these types of alterations. In this case report, we show how it is possible to correct a third-class skeletal malocclusion associated with a posterior bilateral crossbite in a young woman using a rapid expander on miniscrews and fixed orthodontic device to finalise the process. The procedure for the insertion of the palatal screws was aided by the use of a digitally printed surgical guide, and the appliance was applied in the same sitting thanks to the use of a digital flow software and a systematic easy driver. The CBCT scans show how the orthopaedic expansion of the upper maxilla was obtained without any important alterations that damaged the permanent teeth. This case report wishes to demonstrate how easy and predictable it can be to resolve cases of this type with optimal aesthetic and functional results even when body growth has ended.